Improved methanol barrier property of Nafion hybrid membrane by incorporating nanofibrous interlayer self-immobilized with high level of phosphotungstic acid - Abouzari-lotf, Ebrahim Abouzari (American Chemical Society, 2015)
High level of phosphotungstic acid (PWA) was self-immobilized on electrospun nylon nanofiberous sheet to fabricate highly selective methanol barrier layer for sandwich structured proton conducting membranes. Simple tuning for the assembly conditions of central layer and thickness of outer Nafion layers allowed obtaining different composite membranes with superior methanol barrier properties (namely, P = 3.59 × 10-8 cm2 s-1) coupled with proton conductivities reaching 58.6 mS cm-1 at 30 °C. Comparable activation energy for proton transport and more than 20 times higher selectivity than Nafion 115 confirm the effectiveness of the central layer and resulting membranes for application in direct methanol fuel cells (DMFCs). When tested in DMFC single cell, the performance of hybrid membrane was far better than Nafion 115 especially at higher methanol concentrations